Three different [NiFe] hydrogenases confer metabolic flexibility in the obligate aerobe Mycobacterium smegmatis. (25th November 2013) - Berney, Michael; Greening, Chris; Hards, Kiel; Collins, Desmond; Cook, Gregory M.
Summary M ycobacterium smegmatis is an obligate aerobe that harbours three predicted [NiFe] hydrogenases, Hyd1 (MSMEG_2262–2263), Hyd2 (MSMEG_2720‐2719) and Hyd3 (MSMEG_3931‐3928). We show here that these three enzymes differ in their phylogeny, regulation and catalytic activity. Phylogenetic analysis revealed that Hyd1 groups with hydrogenases that oxidize H2 produced by metabolic processes, and Hyd2 is homologous to a novel group of putative high‐affinity hydrogenases. Hyd1 and Hyd2 respond to carbon and oxygen limitation, and, in the case of Hyd1, hydrogen supplementation. Hydrogen consumption measurements confirmed that both enzymes can oxidize hydrogen. In contrast, the phylogenetic analysis and activity measurements of Hyd3 are consistent with the enzyme evolving hydrogen. Hyd3 is controlled by DosR, a regulator that responds to hypoxic conditions. The strict dependence of hydrogen oxidation of Hyd1 and Hyd2 on oxygen suggests that the enzymes are oxygen tolerant and linked to the respiratory chain. This unique combination of hydrogenases allows M. smegmatis to oxidize hydrogen at high (Hyd1) and potentially tropospheric (Hyd2) concentrations, as well as recycle reduced equivalents by evolving hydrogen (Hyd3). The distribution of these hydrogenases throughout numerous soil and marine species of actinomycetes suggests that oxic hydrogen metabolism provides metabolic flexibility in environments with changing nutrient fluxes.